The Impact of Rhetoric on Jerome Frank’s ‘Digestive Jurisprdence’ - Avramović, Dragutin; Jovanov, Ilija (NBP. Nauka, bezbednosti, policija, 2024)
The paper analyses the relationship between law and rhetoric and their intersection areas, particularly focusing on the significance of rhetoric in contemporary judicial proceedings. In the 20th century, the issue of the relationship between law and rhetoric (explicitly or implicitly) became relevant particularly through the scientific excellence of the school of American legal realism, but more recently, it has been somewhat neglected. The authors of this paper devotes particular attention to the judicial decision-making theory of Jerome Frank, a prominent legal realist. It is for his radical positions, as a fact skeptic, that he seems to have unconsciously, subtly but persistently, woven into his works the idea of the importance of rhetoric in judicial decision-making processes. The authors explores the reasons behind Frank’s hesitation for most of his scientific career to give rhetoric (particularly that of Aristotle, which he quoted most) its deserved place. It was only in one of his later works that Frank attempted to build a bridge between his judicial decision-making theory (insisting on the importance of prejudices and subjectivities of a judge to the judicial decision) and rhetoric (aimed at persuading the judge, evoking his emotions, and creating the image of a particular reality in his eyes). It seems that his effort was only a partial success because, even then, he primarily focused on the methods of touching the “souls of the audience”, overlooking the importance of the rhetorical means (primarily logical) that did not lend support for his theory.